Interpretable machine learning prediction of coalbed methane content and depth-dependent predictive contributions in shallow and medium-deep reservoirs: A case study of the Qinshui Basin - Kun Bai; Jian Shen; Wei Li; Sijie Feng; Chen Li; Jiuqing Li; Shuting Cheng; Chenlong Wang (Fuel, 2027)

Role of HIF-1α–SERPINE1 axis in hypoxia–induced trophoblast invasion and its relevance to preeclampsia - Yinglu Zhang; He Dong; Shuting Wang; Feng Zhang; Bin Zhang (Tissue and Cell, 2027)

Causal machine learning uncovers thresholds and seasonal reversal in landscape-meteorology-driven urban Heat-PM₂.₅ coupling - Yiqi Yu; Jie Xu; Shuting Chen; Sidong Huang; Licheng Feng; Wei Cao; Wen Zhou (Sustainable Cities and Society, 2026)

Integrated biological sulfidogenic process: Synergizing sulfate and elemental sulfur reduction for metal-laden wastewater treatment - Jiahua Guo; Junjie Han; Chenxin Zhang; Hao Li; Cheng Li; Shuting Chen; Yibo Wang; Yu Li; Feng Jiang (Water Research, 2026)

Head-to-head comparison of plasma biomarker assays across platforms for amyloid pathology in a multicenter cohort - Xinyi Lv; Kaiyuan Shen; Qianhua Zhao; Guoping Peng; Huayan Liu; Feng Gao; Xiaodong Pan; Wei Chen; Peilin Lu; Haining Zhang; Shuting Zhang; Mengya Xing; et al. (Science Bulletin, 2026)

Influence of beach nourishment on the ecological rehabilitation of sandy beaches: A case study of Beihai Silver Beach on the southern coast of China - Hongshuai Qi; Min Chen; Shuting Zeng; Shunling Wu; Xiaoli Song; Haiqin Duan; Jiayu Li; Feng Cai (Ocean & Coastal Management, 2026)

Long-term assessment of natural mineral-based electrochemical systems for concurrent wastewater treatment and nutrient recovery - Yukun Xing; Shuting Chen; Baile Wu; Xiyuan Feng; Ke Hu; Xiaoxiang Zhang; Junyu Zhou; Jingsheng Shi; Yafei He; Peng Li; Zhengyu Jin (Journal of Water Process Engineering, 2026)

FAK mediates mechanical signaling to maintain epithelial homeostasis through YAP/TAZ-TEADs - Yang Peng; Qiuyun Yuan; Shuting Zhou; Jianguo Gan; Zhengzhong Shen; Xiaoqiang Xia; Yuchen Jiang; Qianming Chen; Yao Yuan; Gu He; Qiang Wei; Xiaodong Feng (Histochemistry and Cell Biology, 2025)

Seismic performance of bolt-connected fully assembled concrete modular construction by full-scale shaking table test - Feng Xiong; Dongdong Zhang; Mingming Ran; Wei Li; Guangyun Kou; Shuting Lei (Engineering Structures, 2025)

The influence of emotion on human thermal comfort: based on netted meta-analysis - Kun Zhou; Hao Yang; ShuTing Li; YaYu Feng; TianYi Pang; YanKai Zhao; Yi Xu (Energy and Buildings, 2025)

Distribution characteristics and influencing factors of benthic diatoms on several typical beaches along the southern coast of China - Min Chen; Jiayu Li; Guobiao Huang; Yanting Lin; Shuting Zeng; Ya Xu; Xuan Liu; Feng Cai; Hongshuai Qi (Marine Environmental Research, 2025)

Fetal weight growth trajectories and childhood development: A population-based cohort study - Xinmei Chen; Hongxiu Liu; Aifen Zhou; Feng Jin; Chufeng Jing; Yuanyuan Li; Wei Xia; Linda G. Kahn; Ya Xie; Xingliang Xiang; Shuting Cao; Wenxin Zhang; et al. (Science Bulletin, 2024)

Retrieval of cloudy land surface temperature from AMSR2 brightness temperature, precipitable water vapour and cloud liquid water - Cheng Huang; Shuting Zhang; Wenjing Han; Xiyue Feng; Si-Bo Duan (International Journal of Remote Sensing, 2024)

The synergistic effect of phototherapy and active substances on hair growth - Shuting Qiu; Zhi Pan; Xiao Jiang; Guowen Lv; Anqi Feng; Hongbo Chen (Journal of Photochemistry and Photobiology B: Biology, 2024)

Selective autophagy receptor p62/SQSTM1 inhibits TBK1-IRF7 innate immune pathway in triploid hybrid fish - Zhenghao Li; Huijuan Zhong; Shuting Lv; Yiru Huang; Shuaibin Pei; Yingbing Wei; Hui Wu; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2024)

Catalytic air oxidation of biogas slurry using Cu sub-nanocluster supported by mesoporous TiZrO4 and protected by SiO2 shell - Jiabai Cai; Huan Li; Wenjia Huang; Shuting He; Kai Feng; Masaki Takaoka (Journal of Hazardous Materials, 2024)

Dynamic Changes of the Infralimbic Cortex and Its Regulation of the Prelimbic Cortex in Rats with Chronic Inflammatory Pain - Longyu Ma; Lupeng Yue; Shuting Liu; Yu Zhang; Meng Zhang; Shuang Cui; Feng-Yu Liu; Ming Yi; You Wan (Neuroscience Bulletin, 2024)
The prelimbic cortex (PL) is actively engaged in pain modulation. The infralimbic cortex (IL) has been reported to regulate the PL. However, how this regulation affects pain remains unclear. In the present study, we recorded temporary hyper-activity of PL pyramidal neurons responding to nociceptive stimuli, but a temporary hypo-function of the IL by in vivo electrophysiological recording in rats with peripheral inflammation. Manipulation of the PL or IL had opposite effects on thermal hyperalgesia. Furthermore, the functional connectivity and chemogenetic regulation between the subregions indicated an inhibitory influence of the IL on the PL. Activation of the pathway from the IL to the PL alleviated thermal hyperalgesia, whereas its inhibition exacerbated chronic pain. Overall, our results suggest a new mechanism underlying the role of the medial prefrontal cortex in chronic pain: hypo-function of the IL leads to hyperactivity of the PL, which regulates thermal hyperalgesia, and thus contributes to the chronicity of pain.

Natural organic small molecules promote the aging of plastic wastes and refractory carbon decomposition in water - Xiangang Hu; Shuting Wang; Ruihong Feng; Kai Hu (Journal of Hazardous Materials, 2024)

Tetracycline and sulfadiazine toxicity in human liver cells Huh-7 - Xuewen Yao; Zhaokang Cheng; Evgenios Agathokleous; Yaqian Wei; Xinyuan Feng; Hanhan Li; Tingting Zhang; Shuting Li; Gaurav Dhawan; Xiao-San Luo (Environmental Pollution, 2024)

Analysis of actual evapotranspiration changes in China based on multi-source data and assessment of the contribution of driving factors using an extended Budyko framework - Tao Su; Shuting Wang; Siyuan Sun; Taichen Feng; Bicheng Huang; Qianrong Ma; Shuping Li; Guolin Feng (Theoretical and Applied Climatology, 2024)

Roles of alcohol group in functionalized carbon nitride for photocatalytic oxidation - Shuting Feng; Xincheng Li; Xianmo Gu; Ruiyi Wang; Yunwei Wang; Zhanfeng Zheng (Fuel, 2024)

Mechanism Interpretation of Sub-critical Crack Growth in Beishan Granite Subjected to Cyclic Loading - Shuting Miao; Peng-Zhi Pan; Zhaofeng Wang; Yujie Feng; Qingsong Zheng (Rock Mechanics and Rock Engineering, 2023)

Highly active complexes of pyrite and organic matter regulate arsenic fate - Shuting Wang; Jingyu Wen; Li Mu; Xiangang Hu; Ruihong Feng; Yuying Jia (Journal of Hazardous Materials, 2023)

Isolation and characterization of an endophytic fungi from Zingiber officinale Rosc. and its activity to promote the growth of tissue culture ginger plantlets in bottles - Shuting Zhang; Yinghong Pei; Jiao Wang; Xiaolong Lin; Zizhong Tang; Lijun Zhou; Tao Chen; Shiling Feng; Chunbang Ding; Yanger Chen; Zhongwei Zhang; Shu Yuan; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Blood-based biomarkers for Alzheimer’s disease: a multicenter-based cross-sectional and longitudinal study in China - Feng Gao; Linbin Dai; Qiong Wang; Chang Liu; Kexue Deng; Zhaozhao Cheng; Xinyi Lv; Yan Wu; Ziyi Zhang; Qingqing Tao; Jing Yuan; Shiping Li; et al. (Science Bulletin, 2023)

Evolution of Meteorological Conditions during a Heavy Air Pollution Event under the Influence of Shallow Foehn in Urumqi, China - Xia Li; Keming Zhao; Shiyuan Zhong; Xiaojing Yu; Zhimin Feng; Yuting Zhong; Ayitken Maulen; Shuting Li (Advances in Atmospheric Sciences, 2023)